Le culte de la blancheur dans la nouvelle “Fairness” de Chinelo Okparanta - Sophie Okunhon (Itinéraires)
The triple meaning of the title of Chinelo Okparanta’s short story “Fairness” (2013) steers the analysis toward issues related to skin color, discrimination and language. Colorism is located at the intersection of three sites of discrimination and oppression: race, class and gender. The text denounces colorism and the harmful effects of a fictional construction of beauty on the bodies and psyche of Nigerian women. The violence of colorism inherent in bleaching and in its ritualistic mutilation of the body is also revealed in the speech acts which expose the heroines’psychological wounds. Language, the purveyor of the “spirit of violence” (Mbembe 2005), possesses the same properties as depigmentation.